A multi-objective optimization model for decision support in water reclamation system planning. (10th December 2019) - Rezaei, Nader; Sierra-Altamiranda, Alvaro; Diaz-Elsayed, Nancy; Charkhgard, Hadi; Zhang, Qiong
Abstract: Water reclamation and reuse not only reduce the negative impacts of wastewater to the environment, but also provide an alternative to withdrawal from natural water resources, forming a closed-loop water supply chain. The design of such a supply chain requires an appropriate sustainability assessment, which simultaneously accounts for economic, environmental, and social dimensions. In this study, a multi-objective optimization model was developed to minimize the costs and carbon footprint (as an environmental indicator), and maximize the value of resource recovery (representing a social benefit) of the water reclamation systems by locating the treatment facility, allocating the treatment capacity, selecting the treatment technology, and allocating customers (final reclaimed water users). The optimizer CPLEX 12.7 was applied and the Triangle Splitting Method was used for the optimization algorithm. The expansion of a water reclamation system in Hillsborough County, Florida was evaluated to illustrate the use of the model. The impacts of population density and elevation variation in the water service area on the model outputs were also investigated. Although the centralization of treatment facilities takes advantage of the economies of scale, the results revealed that simultaneous consideration of economic and environmental indicators favored decentralization of treatment facilities in the study area. This was mainly due to the significant decrease in water transfer requirements, especially in less populous areas. Moreover, the results revealed that contribution of population density to the optimal degree of decentralization of treatment facilities was significant. Graphical abstract: Image 1 Highlights: A multi-objective optimization model for wastewater system management was developed. The optimization model accounted for economic, environmental, and social dimensions. The model favored decentralization of wastewater treatment plants in the study area. Population density influenced the optimal system configuration considerably.